Implementasi Arsitektur Publish And Subscribe Pada Alat Monitoring Suhu Dan Kelembaban Kandang Ular Python Regius Menggunakan NodeMCU (ESP8266) - Habib Zainal Sarif; Mochammad Hannats Hanafi Ichsan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The climatic conditions in the city of Malang, a pretty cool and slightly damp to make some of the pets we have become vulnerable to attack diseases in animals, especially reptiles, especially snakes Pythons regius or commonly known as ball python. In addition to the affected adult Pythons snakes on hormones, decreased appetite the snake can also be influenced by the surrounding temperature and humidity snake cages. For temperature and humidity are ideal for snakes at noon ranged between 27-29 Â° C and for the evening temperature ideally is 23-24 Â° C. As for the moisture is good for these snakes ranged from 50-60%. Although there have been many successful toosl for measuring temperature and humidity of a room but the rancher still needs a tool capable to move so that it is able to keep an eye on the State of the cages despite not being on the enclosure. Based on the issue be made a snake enclosure monitoring system uses a Publish and Subscribe architecture. Where this system is supported by a communication protocol MQTT and will be shown on a Android applications. This research uses 3 parameters of readout of temperature and humidity from sensors DHT11 and time of DS3231 RTC periodically, as the output form of display on the LCD and also on Android applications. For publish and subscribe architecture or send it was chosen because it has the speed and lower power consumption. So that will create an environment that is good for the life of the snake itself.